Pembekalan Kemampuan Dasar Bahasa Inggris bagi Pengrajin dan Penjual Cinderamata di Lombok Barat - Ariani, Sri; Setianingsih, Tri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Art Market Sesela has important role in facilitating the craftsman and souvenir sellers in West Lombok Regency to sell their products. This place also becomes one of the most favorite spot for the tourists to enjoy art performances such as Stick Fighting, and other traditional dances. It is located in Sesela Village, Gunungsari District, West Lombok Regency which is the center of traditional handicraft industry. This Art Market is regularly visited by domestic and foreign tourists. As to provide the maximum service to the tourists, the craftsmen and souvenir sellers should be provided with adequate English language skills. It is indispensable for the craftsmen and souvenir sellers who mostly graduated from elementary school and reluctant to continue their education to the higher level as they cannot afford to pay school fees. As English language is important for the Craftsman and souvenir sellers in supporting their maximum service to the tourists, therefore the Team is intended to provide training of Basic English for them. This is intended to enable the Craftsman and souvenir sellers to communicate in English appropriately. This program is expected to be implemented continually every year.